Regular and Young Investigator Award Abstracts 2021
DOI: 10.1136/jitc-2021-sitc2021.843
|View full text |Cite
|
Sign up to set email alerts
|

843 Development and engineering of human sialidase for degradation of immunosuppressive sialoglycans to treat cancer

Abstract: BackgroundSialoglycans, a type of glycans with a terminal sialic acid, have emerged as a critical glyco-immune checkpoint that impairs antitumor response by inhibiting innate and adaptive immunity. Upregulation of sialoglycans on tumors has been observed for decades and correlates with poor clinical outcomes across many tumor types. We previously showed that targeted desialylation of tumors using a bifunctional sialidase x antibody molecule, consisting of sialidase and a tumor-associated antigen (TAA)-targetin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Another study regarding anti-influenza sialidase inhibitor oseltamivir phosphate found it to reduce the neuraminidase activity of canine mammary cancer cells and contribute to an increase in mammary tumor aggressiveness [ 152 ]. An improvement in the outcome of Leukemia patients has also been observed with neuraminidase inhibitor studies involving oseltamivir and zanamivir [ 153 ].…”
Section: Neuraminidase Inhibitorsmentioning
confidence: 97%
“…Another study regarding anti-influenza sialidase inhibitor oseltamivir phosphate found it to reduce the neuraminidase activity of canine mammary cancer cells and contribute to an increase in mammary tumor aggressiveness [ 152 ]. An improvement in the outcome of Leukemia patients has also been observed with neuraminidase inhibitor studies involving oseltamivir and zanamivir [ 153 ].…”
Section: Neuraminidase Inhibitorsmentioning
confidence: 97%
“…In preclinical studies, sialidase-mediated cleavage of terminal sialic acids improves antitumor immunity by restoring the immune function of exhausted-like T cells and enhancing dendritic cell priming and naïve T cell activation. 1 In multiple syngeneic mouse tumor models, sialidase treatment has demonstrated antitumor activity as monotherapy 1 and additive antitumor activity when combined with anti-programmed death-1 (PD-1)/programmed death-ligand 1 (PD-L1) blockade. E-602 has a wide safety margin, is not an immune agonist and does not stimulate cytokine activation in an in vitro PBMC cytokine release assay.…”
mentioning
confidence: 99%
“…E-602 has a wide safety margin, is not an immune agonist and does not stimulate cytokine activation in an in vitro PBMC cytokine release assay. 1,2 In humans, E-602, via desialylation of tumor cells and immune cells, is expected to have antitumor activity either as monotherapy or in combination with an anti-PD-1 agent. Methods A Phase 1/2, first-in-human, open label, dose escalation and expansion study of E-602 administered as monotherapy and in combination with an anti-PD-1 agent is ongoing to evaluate the safety, pharmacokinetics, pharmacodynamics, and antitumor activity in participants with advanced cancers.…”
mentioning
confidence: 99%